Assessing nitrogen flow in production and utilization cycle of wheat and maize as a tool to monitor N loss in Iran - doi: 10.4025/actascibiolsci.v35i3.16039 (Acta Scientiarum. Biological Sciences, 2013)
Increasing resource use efficiency is crucial for enhancement of agricultural productions and reducing environmental hazards. For this purpose, improvement of Nitrogen use efficiency is an effective approach. Not only N loss occurs in field but also in processing course of food utilization. The objective of this study was to evaluate N loss and efficiency from production to consumption for wheat and maize. For this purpose, data for the amount of applied nitrogen, acreage, yields, amount of returned residue were collected and a proportion of N allocated to different source of food or feed was also traced. Results showed that total N harvested by wheat and maize were 387 and 81.7 kt and N use efficiency for the same crops were 25 and 60%, respectively. Efficiency of N harvested by the crops was different based on the path used. Total N use efficiency in food production cycle for wheat and maize were 14.2 and 7.6%, respectively. Higher efficiency of N was observed in plant food production compared with animal feed. In general, N use efficiency in plant food production system was about 13 times higher than that of feed. For decreasing N loss in food production system, efficiency should be increased in the field and processing courses.